The Effect of Inflation on the Profitability of Islamic Banks An Applied Study on Islamic Banks in Syria for the Period (2010-2018) (Journal of Hama University, 2021)
This study aimed to identify the impact of inflation on the profitability of private Islamic banks in Syria, which was measured by the rate of return on assets and the rate of return on property rights for the period 2010-2018, based on the annual financial statements of Islamic banks published in the Damascus Stock Exchange. On the descriptive approach, the use of statistical methods related to temporal cross-sectional data, and the estimation of the cumulative regression model for the studied Islamic banks using EXCEL and SPSS programs. The study found a positive, statistically significant impact of inflation on the profitability of these Islamic banks.